Robust Performance Assessment of Control Systems with Root Contours Analysis - Karlova-Sergieva Vesela (Cybernetics and Information Technologies, 2025)
Often, in a real practice environment, classical methods for tuning controllers do not provide the desired performance of the control strategy, as they do not account for changes in the parameters of the controlled process. Sometimes, there is no possibility for the rapid implementation of a new control algorithm, and the designer only has access to the current tuning of the introduced parameters. This paper presents an approach for assessing control performance in cases where the controller is designed for nominal operating conditions, aiming to reduce the control error caused by changes in the parameters of the controlled process. A controller with three tuning parameters is considered, with research conducted on the possible correction of the overall proportionality coefficient. The issue of insensitivity and the performance of the transient processes of the closed-loop system is also addressed.